Pengembangan Bahan Ajar Berbasis E-Learning Pada Pembelajaran Tematik Sekolah Dasar - Heni Wijayanti; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
Technology in education, one of which is e-learning, requires the appropriate teaching materials in the implementation of thematic. By using the descriptive qualitative method, the results showed as follows: 1) content expert review is 97%. 2) media expert review is 83%, 3) design expert review 88%, 4) individual product trial is 90%, 5) product group trial is 93%, 6) product trials on students and student responses through questionnaires is 83%. The average score of the overall feasibility test is 89%. With the ‘very good’ feasibility criteria, the product developed is appropriate to be used as supplementary teaching materials in thematic learning.